Stitching Together (in) Anthropology Class : On the Use of Craft Practices in Higher Education Humanities - Arantes, Lydia Maria (FormAkademisk, 2023)
As an anthropologist teaching at a German-speaking Cultural Anthropology and European Ethnology Department (pertaining to a Humanities Faculty), it always struck me how much we know about the role embodiment plays in and for culture and how little we make use of this in teaching. For this reason, I decided to expand established Higher Education pedagogy by putting craft (as a) practice at the centre of my newly developed course entitled DIY in Times of Crisis and Beyond. As a result, my students and I developed our thinking through and while practising embroidery in class, weaving in the mandatory readings and narrations of (pandemic) crafting experiences along the way. Borrowing from the low-threshold approach to stitching in community-based creativity projects, our shared and mostly novice stitching facilitated the articulation of thoughts-in-progress, thus creating a space in which dominant views regarding social (craft) norms, quantifiable productivity as well as academic logocentrism could be temporarily suspended, giving way to embodied wisdom.